Optimization of Universitas Riau Data Network Management Using Software Defined Network (SDN) - Safrianti, Ery; Sari, Linna Oktaviana; Mahan, Rian Arighi (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2019)
Computer networks are one of the main parts in the telecommunications system. To support reliable network technology, a centralized network is needed so that network traffic can be managed more easily. Software-Defined Network (SDN) technology is a centralized network that provides a separation between control planes and data planes in different systems. This study discusses the optimization of network management at the University of Riau (UNRI) using SDN. Optimization is done by designing a UNRI computer network in the form of SDN then simulated using the Mininet. Quality of Service (QoS) analysis is performed from the measurement results using Wireshark. The network simulation results give a delay value of 0.506 ms, 0% packet loss, the throughput of 590,392 Mb / s and jitter of 0.093 ms. The SDN network provides better delay and jitter performance compared to conventional UNRI networks with a delay value of 13,874 ms, 0% packet loss, 635.1 Mb/s throughput and 2.6 ms jitter. UNRI's SDN network design is worth considering because it has better QoS values, delay, and jitter below ITU standards and conventional networks.